2014
DOI: 10.1590/s1983-40632014000300012
|View full text |Cite
|
Sign up to set email alerts
|

Emergência e vigor de mudas de genótipos de mamoeiro em função da irradiância

Abstract: A luminosidade influencia na emergência de sementes e no desenvolvimento inicial do mamoeiro, sendo necessária a identificação do nível de irradiância ideal para o estabelecimento de plântulas e formação de mudas vigorosas. Objetivou-se estudar a emergência de sementes e o vigor das mudas de quatro genótipos de mamoeiro, em diferentes níveis de irradiância. Foram utilizadas sementes de Carica papaya L. dos genótipos híbrido Caliman 01, Golden THB, híbrido triplo e híbrido JS12 x Waimanalo, sob quatro níveis de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In this example, it is more prudent to use d = 15%, which corresponds to X 0 = 7 BEU, which as can be seen, It shows small change in VU (Xi) from this plot size (Table 2). However, larger size is required when considering NL that requires X 0 = 9 seedlings per plot, which approximates to the useful plot size assumed by other researchers in research with seedlings in tubes of other varieties of papaya (SERRANO et al, 2010;PAIXÃO et al, 2012;OLIVEIRA FILHO et al, 2013;SÁ et al, 2013;MENGARDA et al, 2014).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…In this example, it is more prudent to use d = 15%, which corresponds to X 0 = 7 BEU, which as can be seen, It shows small change in VU (Xi) from this plot size (Table 2). However, larger size is required when considering NL that requires X 0 = 9 seedlings per plot, which approximates to the useful plot size assumed by other researchers in research with seedlings in tubes of other varieties of papaya (SERRANO et al, 2010;PAIXÃO et al, 2012;OLIVEIRA FILHO et al, 2013;SÁ et al, 2013;MENGARDA et al, 2014).…”
Section: Resultsmentioning
confidence: 84%
“…This statement can be made especially in relation to LRL since seedlings with very small roots tend to suffer more in the initial stage of growth in the field. In the production of papaya, Serrano et al (2010) in the evaluation of five cultivars, Paixão et al (2012) in the evaluation of 'Golden THB' and, Mengarda et al (2014) in the evaluation of four cultivars, obtained similar results in root length, in the evaluation at 30, 30 and 45 DAS, respectively.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…In trials with production of papaya seedlings in nursery, useful sizes of plots follow the same arbitrariness, also due to the lack of studies on plot designs. Evaluation of experiments with plots sizes of four (Melo et al, 2007), six (Sá et al, 2013), 10 (Paixão et al, 2012Mengarda et al, 2014) and 12 (Serrano et al, 2010) seedlings per plot are reported.…”
Section: Introductionmentioning
confidence: 99%